Effects of different language environments on Chinese graduate students' perceptions of English writing and their writing performance. (April 2017) - Wu, Hongyun; Zhang, Lawrence Jun
Abstract: This paper reports on findings from a study of the impact of language-environments on the second-year Chinese graduate students' English writing perceptions and performance. Ninety-four students were divided into three groups in order to see the effects of language environments on their English writing. One group, a study-abroad group (i.e., ESL learners), consisted of 31 non-English majors, who moved to the U.S. to pursue graduate education. The other two groups were studying for graduate degrees in universities in China. To find out the effects of language environments on their English writing perceptions and performance, we used a self-designed 80-item questionnaire and two writing tests (a letter-writing task and an argumentative essay writing task). Results suggest that in comparison with the at-home group, the ESL language environment had a statistically significant effect on the study-abroad group's English writing perceptions and performance. The study-abroad group was significantly more competent in English letter writing than the two at-home groups ( p ≤ 001). The performance of the study-abroad students was also statistically better than the at-home non-English major group in argumentative essay writing, although they did not outperform the at-home English-major group. Implications of the study are also discussed.